Middle to late cenozoic tectonic events in south and central palawan (philippines) and their implications to the evolution of the south-eastern margin of South China Sea: Evidence from onshore structural and offshore seismic data - Aurelio, M.A. (Elsevier Ltd, 2014)
Using recently gathered onland structural and 2D/3D offshore seismic data in south and central Palawan (Philippines), this paper presents a new perspective in unraveling the Cenozoic tectonic history of the southeastern margin of the South China Sea. South and central Palawan are dominated by Mesozoic ophiolites (Palawan Ophiolite), distinct from the primarily continental composition of the north. These ophiolites are emplaced over syn-rift Eocene turbidites (Panas Formation) along thrust structures best preserved in the ophiolite-turbidite contact as well as within the ophiolites. Thrusting is sealed by Early Miocene (~20Ma) sediments of the Pagasa Formation (Isugod Formation onland), constraining the younger limit of ophiolite emplacement at end Late Oligocene (~23Ma). The onset of ophiolite emplacement at end Eocene is constrained by thrust-related metamorphism of the Eocene turbidites, and post-emplacement underthrusting of Late Oligocene - Early Miocene Nido Limestone. This carbonate underthrusting at end Early Miocene (~16Ma) is marked by the deformation of a seismic unit corresponding to the earliest members of the Early - Middle Miocene Pagasa Formation. Within this formation, a tectonic wedge was built within Middle Miocene (from ~16Ma to ~12Ma), forming a thrust-fold belt called the Pagasa Wedge. Wedge deformation is truncated by the regionally-observed Middle Miocene Unconformity (MMU ~12Ma). A localized, post-kinematic extension affects thrust-fold structures, the MMU, and Late Miocene to Early Pliocene carbonates (e.g. Tabon Limestone). This structural set-up suggests a continuous convergent regime affecting the southeastern margin of the South China Sea between end Eocene to end Middle Miocene. The ensuing structures including juxtaposed carbonates, turbidites and shallow marine clastics within thrust-fold belts have become ideal environments for hydrocarbon generation and accumulation. Best developed in the Northwest Borneo Trough area, the intensity of thrust-fold deformation decreases towards the northeast into offshore southwest Palawan. Â© 2013 Elsevier Ltd.